Systematic Investigation of Resorcin[4]arene‐Based Cavitands as Affinity Materials on Quartz Crystal Microbalances. Issue 3 (23rd March 2017) - Ryvlin, Dimitrij; Dumele, Oliver; Linke, Alexander; Fankhauser, Daniel; Schweizer, W. Bernd; Diederich, François; Waldvogel, Siegfried R.
Abstract: Resorcin[4]arene cavitands are well‐known supramolecular hosts, and their outstanding guest‐binding abilities in solution have been studied in detail in recent decades. In a systematic approach, different resorcin[4]arene cavitands and container molecules are characterized as affinity materials for gravimetric sensing using high‐fundamental‐frequency quartz crystal microbalances. Analysis of their affinity toward a series of various analytes reveals a remarkable dependence of both selectivity and sensitivity on the shape, accessibility, and size of the cavity, along with their supramolecular interactions with the host molecules. Abstract : Cavitand sensors : In a systematic approach, different resorcin[4]arene‐based cavitands and container molecules and their supramolecular properties are investigated through gravimetric sensing with high‐fundamental‐frequency quartz crystal microbalances (HFF‐QCMs). The characteristics of the voids are essential for their performance as affinity materials in sensor applications (see figure).